Feed additives containing sequestrant clay minerals and inactivated yeast reduce aflatoxin excretion in milk of dairy cows - Rodrigues, R. O. [UNESP]; Ledoux, D. R.; Rottinghaus, G. E.; Borutova, R.; Averkieva, O.; McFadden, T. B. (Elsevier B.V., 2019)
The objective was to evaluate the efficacy of 2 dietary mycotoxin sequestrants, Toxy-Nil (TN) or Unike Plus (UP), in reducing aflatoxin (AF) M1 concentrations in milk of dairy cows challenged with dietary AF. Thirty-two mid-lactation Holstein cows were blocked by parity, days in milk, and milk yield and were randomly assigned within block to receive one of the following treatments: (1) 2.8 mg of AF/cow per d (positive control, PC), (2) 2.8 mg of AF + 100 g of TN/cow per d, (3) 2.8 mg of AF + 100 g of UP/cow per d, or (4) no AF and no additives (negative control, NC). For 7 d, treatments, dispersed in 150 g of sweet feed carrier, were top-dressed twice daily by mixing into the top portion of the TMR at each feeding. After the experimental period, cows were fed the NC diet and clearance of AFM1 via milk was monitored for 7 d. Feed and water were available ad libitum throughout the trial. Treatments had no effect on feed intake, milk yield, milk composition, or milk somatic cell count. Relative intake of AF was similar among PC, TN, and UP, averaging 106.5, 107.6, and 102.5 +/- 2.9 mu g/kg of diet dry matter, respectively. Relative intake of mycotoxin sequestrants was similar between TN and UP, averaging 0.4 and 0.4 +/- 0.1% of diet dry matter, respectively. Concentration and mass of AFM1 secreted in milk and in urine were similar between TN and UP, but were lower than PC; concentrations in milk averaged 0.2, 0.3, and 0.6 +/- 0.1 mu g/kg, respectively, and mass secreted in milk averaged 8.1, 9.8, and 20.5 +/- 1.7 mu g/d. Concentrations in urine averaged 6.9, 7.4, and 14.2 +/- 1.5 mu g/L, respectively, and mass secreted in urine averaged 225.7, 250.8, and 521.6 +/- 53.1 mu g/d. Likewise, concentration and mass of free AF excreted in feces were similar between TN and UP, but were lower than PC; concentrations averaged 7.7, 8.9, and 12.4 +/- 0.6 mu g/kg, respectively, and mass excreted averaged 57.8, 69.6, and 95.6 +/- 4.8 mu g/d. Transfer of AF from feed to AFM1 in milk was reduced by 63 and 52%, and in urine, by 57 and 52% for TN and UP, respectively. Transfer of AF from feed to free AF in feces was reduced by 38 and 26% for TN and UP, respectively. The clearance rate of AFM1 in milk did not differ among PC, TN, and UP (46.1, 66.5, and 50.0 +/- 6.7%/d, respectively). Results indicate that dietary inclusion of 100 g of TN or UP significantly reduced AFM1 in milk of cows consuming TMR containing approximately 105 mu g of AF/kg of diet dry matter. Results also suggest that both TN and UP reduced absorption of AF.
Keywords: adsorbent; aflatoxin M-1; mycotoxin